Pulmonary function among stone quarry workers in India: The effect of duration of exposure, smoking status and job profile on pulmonary function tests - Junaid Aziz Sheikh; Zahid Ali Khan; Tazeen Khan; Sumaira Chowdhary (Journal of Health and Social Sciences)
Introduction: Despite advances in technology, in India workers of stone processing industry continue to be at high risk for lung function deterioration. This study was designed to analyse the effect of duration of exposure, job profile and smoking on lung function of stone quarry workers from Jammu city, Jammu and Kashmir State, India. Methods: A cross-sectional study was carried out among 100 male stone crusher workers, selected through multi-stage random sampling technique. Effect of risk factors on the pulmonary function tests of the workers was analysed by ‘Students independent t-test’, one-way ANOVA and simple linear regression. The significance threshold was set up at P < 0.05. Results: We observed a significant reduction in lung function in subjects having duration of exposure above 10 years (Group III) with respect of stone crushers with duration of exposure up to 5 years (Group I) and 6 to 10 years of exposure (Group II). Lung function tests revealed a statistically significant (P < 0.05) reduction in lung function test parameters among manual workers compared to non-manual group of workers and among smokers compared to non-smokers. However, simple linear regression analysis revealed that only increase in duration of silica dust exposure was significantly associated with a reduction in pulmonary function tests, specifically in FVC (P = 0.019), FEV3 needs to be as subscript (P = 0.016), FEF25 (P = 0.016), FEF0.2-1.2 (P = 0.048), PEFR (P = 0.019) and MVV (P = 0.001) values. Conclusion: Duration of silica dust exposure is the most important determinant of pulmonary function deterioration. Therefore, limiting cumulative silica dust exposure can effectively reduce damage to airways in silica-exposed workers.